PENERAPAN METODE BERNYANYI DALAM PEMBELAJARAN ANAK USIA 5–6 TAHUN DI TK SANTO YOSEPH NAIKOTEN II KUPANG - Celian Dede, Stefania; Theodorina Novyani Seran; Yohana Yuniati; Credo G. Betty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine how the singing method is implemented in learning activities for children aged 5-6 years at TK Santo Yoseph Naikoten II Kupang. The singing method is one of the learning methods that uses songs as a medium for delivering learning materials, making the learning process more interesting and enjoyable for early childhood learners. This research used a qualitative descriptive approach. Data collection techniques included observation, interviews, and documentation. The research informants consisted of the group B classroom teacher as the main data source and children aged 5-6 years as supporting data sources. The results showed that the implementation of the singing method in learning activities was carried out in a planned and systematic manner through opening, core, and closing activities. Teachers adjusted the songs to the learning themes and children's characteristics and used audio-visual media such as laptops, speakers, and song videos to support singing activities. In addition, teachers guided the singing activities using movements, clapping, and facial expressions so that children became more focused, active, enthusiastic, and confident during the learning process. Thus, the singing method was able to create a fun learning atmosphere that suited the characteristics of early childhood learners. Keywords: singing method, early childhood learning, children aged 5-6 years, early childhood education